Polymer-assisted PD-L1 degradation and targeted photodynamic therapy synergize to suppress immunodeficient tumors - Changyong Guo; Shipeng He; Huaxing Shen; Wei Cong; Jinqiu Li; Yajing Ji; Wenjing Huang; Fei Gao; Honggang Hu (Acta Pharmaceutica Sinica B)
Checkpoint blockade immunotherapy has emerged as a transformative approach in cancer treatment by activating tumor-infiltrating T cells. However, the efficacy of PD-L1 blockade is restricted in “cold” tumors, which are characterized by low immunogenicity, presenting a challenge to immunotherapy. This study introduces an innovative strategy, utilizing cathepsin-cleavable N-(2-hydroxypropyl) methacrylamide (HPMA) polymer-assisted combined photodynamic therapy (PDT) and PD-L1 degradation for the first time, effectively treating T cell-deficient tumors. The degradable main-chain polymer, conjugated with photosensitizer porphyrin, facilitates the accumulation of reactive oxygen species (ROS), triggering immunogenic cell death (ICD) and promoting cytotoxic T lymphocytes (CTLs) infiltration into tumors. Multivalent peptide antagonists of PD-L1 promote PD-L1 degradation in lysosomes through receptor crosslinking, overcoming the adaptive cycling of PD-L1 to the tumor cell surface. These findings demonstrate that polymer-assisted PDT and PD-L1 crosslinking degradation represent a potential novel strategy for anti-tumor immunotherapy, providing valuable tools for expanding immunotherapy applications in immunosuppressive cancers.